(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The study aimed to survey the views of a group of Syrian university students about the values of human citizenship that should be included in the media discourses of private satellite channels in the Syrian Arab Republic, by classifying these values within two fields (personal values- and national values), using the descriptive and analytical approach on a sample of students Faculties of Media and Political Science at Damascus University. A questionnaire consisting of (17) statements was designed with a triple correction key, and after performing the appropriate statistical treatments, the study concluded that the degree of the study sample’s assessment of the necessity to include the media discourse of the private Syrian satellite channels for citizenship values was average, and the results showed no effect of the study variables (gender, year The study, specialization) is based on the opinions of the study sample individuals that the media discourse of private Syrian satellite channels must include the values of citizenship.